2019
DOI: 10.1080/14756366.2019.1626375
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of anti-protozoan activity of nitroaromatic benzenesulfonamides inhibiting carbonic anhydrases fromTrypanosoma cruziandLeishmania donovani

Abstract: Chagas disease and leishmaniasis are neglected tropical disorders caused by the protozoans Trypanosoma cruzi and Leishmania spp. Carbonic anhydrases (CAs, EC 4.2.1.1) from these protozoans (α-TcCA and β-LdcCA) have been validated as promising targets for chemotherapic interventions. Many anti-protozoan agents, such as nitroimidazoles, nifurtimox, and benznidazole possess a nitro aromatic group in their structure which is crucial for their activity. As a continuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 60 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Overall, the very interesting moieties present in the NP coumarins make them a source of inspiration for medicinal chemists and pharmacologists in the search of new drugs with a safer profile and specific action in a variety of disorders, starting from the infective ones 79 and ending with tumours 80 and inflammatory diseases 81 . For the moment, only the human a-CAs were investigated for their inhibition profile with coumarins, but such enzymes are also present in other organisms, such as pathogenic bacteria, protozoans, and fungi [82][83][84][85] . Investigation of coumarin derivatives (including NPCs) against these enzymes may thus lead to interesting developments in the fight of infections produced by such pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the very interesting moieties present in the NP coumarins make them a source of inspiration for medicinal chemists and pharmacologists in the search of new drugs with a safer profile and specific action in a variety of disorders, starting from the infective ones 79 and ending with tumours 80 and inflammatory diseases 81 . For the moment, only the human a-CAs were investigated for their inhibition profile with coumarins, but such enzymes are also present in other organisms, such as pathogenic bacteria, protozoans, and fungi [82][83][84][85] . Investigation of coumarin derivatives (including NPCs) against these enzymes may thus lead to interesting developments in the fight of infections produced by such pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…nifurtimox which has severe limitations mainly in the chronic phase of the infection [28]. Several compounds were tested in order to identify their activity, including those from the class of nitroaromatics [29]. Indeed, interest in molecules containing the nitro group has undergone a resurgence in recent years, due to a greater understanding of the role of nitro-reductases involved in their activation and also on the mechanisms by which parasites develop resistance [30].…”
Section: Plos Onementioning
confidence: 99%
“…In the recent past, CAs belonging to the β -CA family have emerged as potential targets for developing drugs against diseases caused by bacterial and parasitic pathogens. Indeed, several in vitro inhibition studies have shown that the β -CAs from pathogenic bacteria and parasitic pathogens can be inhibited by certain compounds [12,13,14,15,16,17,18,19,20,21,22,23,24]. Among these inhibitors are sulfonamides and their bioisosteres, which are the main classes of CA inhibitors that have been in clinical use for more than 50 years [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%